Thimerosal allergy and clinical relevance in Thailand - Penpun Wattanakrai (2018)
Background: Thimerosal or merthiolate is used as an antiseptic and a preservative in topical medicaments, cosmetics, and vaccines. Thimerosal is known to cause delayed type hypersensitivity. However, there is argument about the clinical relevance and risk of using thimerosal-preserved products in thimerosal allergic individuals. Objective: Retrospective review of patch test results from the Ramathibodi Hospital patch test clinic to determine the prevalence and relevance of allergic reactions to thimerosal in Thailand. Material and Method: During a 5-year period, thimerosal was patch tested in all patients tested for possible allergic contact dermatitis. Thimerosal was the second most common allergen causing a positive patch test reaction. Results: Of the 433 patients tested, 46 (10.62%) were positive to thimerosal. However, despite the high prevalence of positive reactions none was clinically relevant to their present dermatitis, none of the patients reported reactions to vaccination or cross-reaction to piroxicam. Conclusion: There was a high rate of sensitization to thimerosal in Thai patients, but were of little clinical relevance. The author does not advise thimerosal allergic individuals to avoid vaccination, although the small risk of local dermatitis should be pointed out. The topical use of thimerosal containing antiseptics should be avoided.